Հայ տպագիր ժառանգությունը պատմության հոլովույթում - Տիգրան Զարգարյան; Հայկանուշ Ղազարյան; Մայա Գրիգորյան (ՀՀ ԳԱԱ հրատ.)
В Национальной библиотеке продолжаются работы над созданием баз данных “Армянская книга” и “Армянская пресса”, целью чего является сосредоточение и обобщение в них истории армянской книги и прессы, биографий авторов, редакторов и издателей, а также сведения об издательствах. Всевозможными методами (сканирование, загрузка с различных сайтов, дар от авторов или издателей) приобретаются оцифрованные копии книг и периодики и прикрепляются к библиографическим записям для чтения онлайн. The National Library continues working on the creation of the database of «Armenian Books» and «Armenian Press». The porpose to concentrate and summarize the history of Armenian books and press, biographies of authors, editors and publishers, as well as information on the publishing houses. By various methods (scanning, downloading from various sites, also from gifts of the authors or publishers) copies of books and periodicals are thus being acquired, digitized and attached to the bibliographic records for online reading.
Keywords: Bibliography; Library Science; Information Science; Information resources; Electronic information resources